Application of Teaching Material Science of SSI to Analyze Science Literature Students in Online Learning - Nainggolan, Ninda Yera Setyo; Sutikno, Sutikno; Linuwih, Suharto (Universitas Negeri Semarang, 2022)
Learning in 2021 is a period of understanding with the help of online learning. Where online learning will affect the level of student ability. One of them is scientific literacy skills. one way to see students' scientific literacy skills is with socio-scientific issues on optical material. This study uses quantitative methods with class VIII C at SMPIT AL-MADANI. The result of this research is that the aspect of Science as the body of knowledge gets a score of 0.71. The aspect of Science as a way of thinking got a score of 0.72. The science aspect as a way of investigating got a score of 0.70, and the science aspect as a mastery of the interaction competence of Science, technology, and society got a score of 0.69. The average obtained is 0.70, with sufficient criteria. It can conclude that class VIII C students have sufficient scientific literacy skills after learning using the help of socio-scientific integrated science teaching materials.